G487(P) Fact or fiction? brain herniation after hypoxic-ischaemic events in neonatal patients. (24th May 2017) - McAllister, J; Mahaveer, A; Gottstein, R
Abstract : Aims: Conventional teaching in neonatology is that open cranial sutures protect newborns from brain herniation secondary to raised intracranial pressure. This case series aims to disseminate observations from a tertiary neonatal centre of brain herniation in newborns following hypoxic-ischaemic injury. Methods: A retrospective review of case notes of patients admitted to the neonatal intensive care unit who were found to have brain herniation on MRI scan was performed using Badger. Their clinical history and imaging reports were recorded. A literature search was conducted using Ovid Medline to find previous case reports of neonatal brain herniation. Results: Three cases of neonatal brain herniation associated with hypoxic-ischaemic events occurred from 2015 to 2016. Baby A was a term baby who experienced profound perinatal hypoxia requiring resuscitation followed by therapeutic hypothermia. An MRI brain scan showed uncal and cerebellar tonsil herniation. After parental discussion care was then orientated to palliation. Baby B was a 23 week gestation infant transferred from another hospital at 49 weeks corrected gestational age for a surgical opinion. On the unit, he arrested and was resuscitated. An MRI head showed cerebral oedema and coning through the tentorium cerebelli and foramen magnum. Baby C was a term baby with apnoea and hypotonia requiring intubation at delivery. An MRI brain and spine at one month showed hydrocephalus, obstruction at the foramen magnum and an atrophic inferior brainstem likely due to antenatal ischaemia. This patient was then transferred to a local unit for palliative care. The literature search found six case reports of neonatal brain herniation. These were secondary to lumbar puncture, infarction, intracranial bleeding, meningitis and tumour. No reports of herniation due to hypoxic-ischaemic events were identified. Conclusion: The paucity of case reports of neonatal brain herniation confirms that this pathology is rare but possible. Observation of three cases of brain herniation associated with hypoxic-ischaemic events in two years indicates that this serious pathology should be considered in patients with abnormal neurology following a hypoxic-ischaemic event. Diagnosis on MRI scan is valuable for guiding further care towards palliation where appropriate.